THE EFFECT OF AGE AND SLAUGHTER WEIGHT ON CARCASS AND NON CARCASS OF LOCAL FEMALE SHEEP - Siti Muyasaroh (Bantara Journal of Animal Science, 2019)
The study was conducted to determine the effect of age and slaughter weight on carcass and non carcass (head, skin, legs, heart, liver, lugs and digestive tract) of local female sheep. The study was conducted on sixty local female sheep consisted thirty local female sheep with slaughter weight of 10-14.99 kg and thirty local female sheep with slaughter weight of 15-20 kg, are less than one year, 1-1.5 years, and 1.5-2 years. Data collected including age, slaughter weight, carcass weight, non carcass weight (head, skin, legs, hear, liver, lungs and digestive tract), carcass percentage and non carcass percentage. The method used was factorial pattern. The analysis shows that the slaughter weight gives very significant effect on carcass, skin, lung, liver, heart Data was analysed by analysis of variance of factorial pattern. The statistic result showed that slaughter weight significantly (P<0.05) affected carcass and non carcass percentage. Age significantly (P<0.05) affected carcass percentage, skin percentage, lung percentage, heart percentage, liver percentage, lungs percentage and digestive tract percentage. In this study it can be concluded that there is a significant effect between the slaughter weight to carcass and non carcass percentage, except head percentage. There is no connection between age and slaugher weight on carcass and non carcass percentage of local female sheep. Therefore it could be concluded that slaughter weight significantly affects carcass and non carcass, and in particular, age significantly affected carcass and non carcass percentage, except head percentage. There was no interaction between age and slaughter weight on the carcass percentage.